Analysis of Electricity Demand to Increase the Electrification Ratio (Case Study: Madura Island) - Addin Aditya; Erma Suryani; Rully Agus Hendrawan (Institut Teknologi Sepuluh Nopember, 2017)
Abstract- One of the Indonesia’s problem as an archipelago is uneven electrification ratio in the entire of archipelago. Especially for small and isolated island are not effectively to build a large power plant due the ratio between population and investment are immense. In here, a strategy to increase the electrification ratio in the islands is a challenge for Indonesia Government. In this research will be used the dynamic model approach to analyze the demand of electrical energy in Madura Island to increase the electrification ratio in the Indonesia’s Islands. The result shows that the growth of electricity demand in Madura Island is 9% and the most important factor that affecting electrification ratio in Madura is number of electricity customer and power plant capacity to increase the electrification ratio.